2018
DOI: 10.1016/j.electacta.2018.04.190
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Nicarbazin derived platinum group metal-free electrocatalyst in scalable-size air-breathing cathodes for microbial fuel cells

Abstract: In this work, a platinum group metal-free (PGM-free) catalyst based on iron as transitional metal and Nicarbazin (NCB) as low cost organic precursor was synthesized using Sacrificial Support Method (SSM). The catalyst was then incorporated into a large area air-breathing cathode fabricated by pressing with a large diameter pellet die. The electrochemical tests in abiotic conditions revealed that after a couple of weeks of successful operation, the electrode experienced drop in performances in reason of electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 96 publications
(167 reference statements)
0
10
0
Order By: Relevance
“…Activated carbon seems to be the right choice since it is cost-effective, commercially available and durable over long terms operations [66,67]. In the past decade, PGM-free catalysts based on transition metals have also gained attention worldwide due to higher catalytic activity compared to both platinum and carbonaceous catalysts [68,69]. Large-scale production and relatively high costs still prevent its commercial implementation [54].…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon seems to be the right choice since it is cost-effective, commercially available and durable over long terms operations [66,67]. In the past decade, PGM-free catalysts based on transition metals have also gained attention worldwide due to higher catalytic activity compared to both platinum and carbonaceous catalysts [68,69]. Large-scale production and relatively high costs still prevent its commercial implementation [54].…”
Section: Introductionmentioning
confidence: 99%
“…Highly active and durable iron–nicarbazin derived electrocatalyst (Fe‐NCB) was originally developed for future automotive applications synthesised from iron nitrate and nicarbazin (NCB) as iron salt and nitrogen rich organic precursor . Fe‐NCB was successfully used in a recent MFC study and was shown to be a promising ORR catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…PGM-free materials are catalysts containing an earth abundant transition metal such as Fe, Co, Mn or Ni [ [45] , [46] , [47] ]. High performing PGM-free can be categorized into two main groups; the first one that use catalysts produced through pyrolysis (high temperature treatment in controlled atmosphere) of a nitrogen-rich organic precursor and a metal-containing salt [ [48] , [49] , [50] , [51] , [52] ] and the second one through deposition or impregnation of organic molecules with the metal incorporated into their structure such as porphyrins or phthalocyanines [ [53] , [54] , [55] , [56] ]. Generally, it was previously found that iron was the most active and efficient [ 57 ].…”
Section: Introductionmentioning
confidence: 99%